2011
DOI: 10.1080/10440046.2011.606490
|View full text |Cite
|
Sign up to set email alerts
|

Oat and Oat-Vetch as Rainfed Fodder-Cover Crops in Semiarid Environments: Effects of Fertilization and Harvest Time on Forage Yield and Quality

Abstract: We evaluate the forage yield and quality, species composition, and carrying capacity of oats and oat-vetch as fodder-cover crops, grown in almond orchards, under mineral or organic fertilizer and three harvesting regimes ("grazing," "hay," and "grain plus straw"). Also, we show preliminary results of almond yield. Differences in yield due to mineral and organic fertilization were only 9%. The carrying capacity was similar for all treatments. The almond yield was greater when the cover crop was removed early as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…However, there is a concern among farmers about the yield effect of water competition with the main crop, particularly in rainfed systems. Yet, these possible impacts can be overcome by an adequate timing of cover crop management operations, while the farm may have an additional output in the form of forage if the cover is grazed (Ramos et al 2011).…”
Section: Cover Cropsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is a concern among farmers about the yield effect of water competition with the main crop, particularly in rainfed systems. Yet, these possible impacts can be overcome by an adequate timing of cover crop management operations, while the farm may have an additional output in the form of forage if the cover is grazed (Ramos et al 2011).…”
Section: Cover Cropsmentioning
confidence: 99%
“…80 % of total fuelwood consumed in Spain in the year 2000 (Infante-Amate et al 2014). In addition, cover crops can be established below the trees protecting the soil from erosion, contributing to soil carbon sequestration (González-Sánchez et al 2012;Aguilera et al 2013a) and potentially serving as animal feed (Ramos et al 2011). In spite of these promising features, there is some concern about the temporal limitation of soil carbon sequestration, which would only occur until a new equilibrium is reached.…”
Section: Introductionmentioning
confidence: 99%
“…The legume-grass combination has been used in several mixed cropping systems including forage and cover crops (Karpenstein-Machan and Stuelpnagel, 2000;Rauber et al, 2001;Ramos et al, 2011). Generally, grasses in mixed cropping with legumes uptake more N than in sole cropping, because of transfer from rhizodeposit-N of legume to the associated grass (Xiao et al, 2004;Rasmussen et al, 2007).…”
mentioning
confidence: 99%
“…Others also reported high total N contributions from legume CCs (Mansoer et al, 1997). Ramos et al (2011) reported in a previous study that two cover crop (oat-vetch-Vicia sativa L. and oat-Avena sativa L.) treatments increased total N (32.5%) according to control. Similarly, greater N accumulation by hairy vetch compared to non-legume CCs like cereal rye, austrian winter pea (Lathryrus hirsutus L.), annual ryegrass (Lolium multiflorum Lam.…”
Section: Total Nmentioning
confidence: 90%